PENGARUH KEDISIPLINAN DAN KUALITAS KERJA TERHADAP PRESTASI KARYAWAN PADA PT PERKASA BETON BATAM - Aztamara, Reo Rizky; Saputra, Asron (SCIENTIA JOURNAL, 2019)
Employees in a company that have good work performance are valuable assets for the company, each company must have dreams and hopes to build good work performance so that the company can compete in its business. Work discipline and work quality are several factors that can affect the work performance of employees in a company. This study aims to determine whether there is an influence between discipline, and work quality on employee work performance at PT Perkasa Beton Batam. Oppo in this research were employees of PT Perkasa Beton Batam with a sample size of 101 people. This research method is quantitative causality research and uses multiple regression analysis. The results of the study showed that discipline and quality of work partial had a significant influence on the performance of employees of PT Perkasa Beton Batam. Partially discipline and work quality are two factors that can jointly influence employee performance, and work quality has a significant effect on employee performance. So it can be concluded that discipline and work quality are two factors that can jointly influence employee performance.